Analysis of the sensible and total ventilation energy recovery potential in different climate conditions. Application to the Spanish case. (25th February 2019) - Ribé, O.; Ruiz, R.; Quera, M.; Cadafalch, J.
Highlights: Simple decision tool for heat recovery ventilators planners. Transient model based on hourly values of the climatic data. Results presented in simple isoline maps and tables. Application to the Spanish area considering 48 locations. Abstract: Energy recovery elements play a major role in the efficiency and sustainability of building ventilation systems. The use of a sensible or total energy recovery ventilator is a key decision for ventilation systems designers. However, there is a lack of technical tools and developments to support this decision. The authors present a procedure to develop a simple decision tool for designers based on hourly values of the outdoor weather conditions and that can be applied to any kind of building. Results of the procedure are presented in simple-to-use isoline maps and tables. In order to assess credibility of the model used in the procedure, data published in the literature have been used as a reference, showing good accordance. As an example, the procedure has been applied to the Spanish area considering 48 different locations. Results have been presented and discussed. Their analysis shows as the market-accepted recommendation of using energy recovery ventilators in locations with high relative humidity during the summer should be reconsidered.